The contextual theology of Kosuke Koyama and its contribution to Asian theology. - Vergara, Wenifredo B. (Singapore : Southeast Asia Graduate School of Theology, 1985)
The purpose of this paper is to present, analyze and critically evaluate the theology of Kosuke Koyama in so far it attempts to offer a fresh, relevant and unique way of doing theology in Asia.
Thesis (M.Theo.) - South East Asia Graduate School of Theology